Cofilin is a mediator of RET-promoted medullary thyroid carcinoma cell migration, invasion and proliferation. (15th September 2019) - Giardino, E.; Catalano, R.; Barbieri, A.M.; Treppiedi, D.; Mangili, F.; Spada, A.; Arosio, M.; Mantovani, G.; Peverelli, E.
Abstract: Medullary thyroid carcinoma (MTC) is a rare neuroendocrine tumor that originates from parafollicular thyroid C cells and accounts for 5% of thyroid cancers. In inherited cases of MTC, and in about 40% of sporadic cases, activating mutations of the receptor tyrosine kinase proto-oncogene RET are found. Constitutively active RET triggers signaling pathways involved in cell proliferation, survival and motility, but the mechanisms underlying malignant transformation of C-cells have been only partially elucidated. Cofilin is a key regulator of actin cytoskeleton dynamics. A crucial role of cofilin in tumor development, progression, invasion and metastasis has been demonstrated in different human cancers, but no data are available in MTC. Interestingly, RET activation upregulates cofilin gene expression. The aim of this study was to investigate cofilin contribution in invasiveness and growth of MTC cells, and its relevance in the context of mutant RET signaling. We found that cofilin transfection in human MTC cell line TT significantly increased migration (178 ± 44%, p < 0.001), invasion (165 ± 28%, p < 0.01) and proliferation (146 ± 18%, p < 0.001), accompanied by an increase of ERK1/2 phosphorylation (2.23-fold) and cyclin D1 levels (1.43-fold). Accordingly, all these responses were significantly reduced after genetic silencing of cofilin (−55 ± 10% migration, p < 0.001, −41 ± 8% invasion, p < 0.001, −17 ± 3% proliferation, p < 0.001). These results have been confirmed in primary cells cultures obtained from human MTCs. The inhibition of constitutively active RET in TT cells by both the RET pharmacological inhibitor RPI-1 and the transfection of dominant negative RET mutant (RETΔTK) resulted in a reduction of cofilin expression (−37 ± 8%, p < 0.001 and −31 ± 16%, p < 0.01, respectively). Furthermore, RPI-1 inhibitory effects on TT cell migration (−57 ± 13%, p < 0.01), but not on cell proliferation, were completely abolished in cells transfected with cofilin. In conclusion, these data indicate that an unbalanced cofilin expression, induced by oncogenic RET, contributes to promote MTC invasiveness and growth, suggesting the possibility of targeting cofilin pathway for more effective treatment of MTC. Highlights: In MTC cells oncogenic RET induced an increase of cofilin expression. Cofilin overexpression increased MTC cell invasion and proliferation. Cofilin silencing inhibited MTC cell invasion and proliferation. Cofilin pathway may represent a new possible therapeutic target for MTC.